The American Society for Clinical Pathology's 2014 Vacancy Survey of Medical Laboratories in the United States. Issue 3 (1st September 2015) - Garcia, Edna; Ali, Asma M.; Soles, Ryan M.; Lewis, D. Grace
Abstract: Objectives: To determine the extent and distribution of workforce shortages within the nation's medical laboratories. Historically, the results of this biennial survey have served as a basis for additional research on laboratory recruitment, retention, education, marketing, certification, and advocacy. Methods: The 2014 Vacancy Survey was conducted through collaboration between American Society for Clinical Pathology's Institute of Science, Technology, and Policy in Washington, DC, and the Evaluation, Measurement, and Assessment Department and Board of Certification in Chicago, Illinois. Data were collected via an Internet survey that was distributed to individuals who were able to report on staffing and certifications for their laboratories. Results: Data reveal increased overall vacancy rates since 2012 for all departments surveyed except cytology and cytogenetics. Also, results show higher anticipated retirement rates for both staff and supervisors. Overall certification rates are highest among laboratory personnel in cytogenetics, hematology/coagulation, and flow cytometry departments and lowest among phlebotomy, specimen processing, and anatomic pathology. Conclusions: Factors such as retirement and the improving economy are driving the need for more laboratory professionals. Recruitment of qualified laboratory professionals in the workforce and students in laboratory programs will be the key in fulfilling the higher vacancies revealed from the survey results in 2014.